Insights into the poor prognosis of allopurinol-induced severe cutaneous adverse reactions: the impact of renal insufficiency, high plasma levels of oxypurinol and granulysin. Issue 12 (12th August 2014) - Chung, Wen-Hung; Chang, Wan-Chun; Stocker, Sophie L; Juo, Chiun-Gung; Graham, Garry G; Lee, Ming-Han H; Williams, Kenneth M; Tian, Ya-Chung; Juan, Kuo-Chang; Jan Wu, Yeong-Jian; Yang, Chih-Hsun; Chang, Chee-Jen; et al.
Abstract : Objective: Allopurinol, an antihyperuricaemic agent, is one of the common causes of life-threatening severe cutaneous adverse reactions (SCAR), including drug rash with eosinophilia and systemic symptoms (DRESS), Stevens–Johnson syndrome (SJS) and toxic epidermal necrosis (TEN). The prognostic factors for allopurinol-related SCAR remain unclear. This study aimed to investigate the relationship of dosing, renal function, plasma levels of oxypurinol and granulysin (a cytotoxic protein of SJS/TEN), the disease severity and mortality in allopurinol-SCAR. Methods: We prospectively enrolled 48 patients with allopurinol-SCAR (26 SJS/TEN and 22 DRESS) and 138 allopurinol-tolerant controls from 2007 to 2012. The human leucocyte antigen ( HLA ) -B*58:01 status, plasma concentrations of oxypurinol and granulysin were determined. Results: In this cohort, HLA-B*58:01 was strongly associated with allopurinol-SCAR (p<0.001, OR (95% CI) 109 (25 to 481)); however, the initial/maintenance dosages showed no relationship with the disease. Poor renal function was significantly associated with the delayed clearance of plasma oxypurinol, and increased the risk of allopurinol-SCAR (p<0.001, OR (95% CI) 8.0 (3.9 to 17)). Sustained high levels of oxypurinol after allopurinol withdrawal correlated with the poor prognosis of allopurinol-SCAR. In particular, the increased plasma levels of oxypurinol and granulysin linked to the high mortality of allopurinol-SJS/TEN (p<0.01), and strongly associated with prolonged cutaneous reactions in allopurinol-DRESS (p<0.05). Conclusions: Impaired renal function and increased plasma levels of oxypurinol and granulysin correlated with the poor prognosis of allopurinol-SCAR. Allopurinol prescription is suggested to be avoided in subjects with renal insufficiency and HLA-B*58:01 carriers. An early intervention to increase the clearance of plasma oxypurinol may improve the prognosis of allopurinol-SCAR.